Norfloxacin La(III)-based complex: Synthesis, characterization, and DNA-binding studies - Shaban, Shaban Y.; El-Kemary, Maged A.; Samir, Gehan; El-Baradei, Hosny; Puchta, Ralph (Journal of Coordination Chemistry, 2015)
A La(III) complex, [LaIIICl2(NOR)2]Cl (2), containing norfloxacin (NOR) (1), a synthetic fluoroquinolone antibacterial agent, has been synthesized and characterized by elemental analysis, IR, UV-vis spectra and 1H NMR spectroscopy, and molar conductance measurements. The interaction between 2 and CT-DNA was investigated by steady-state absorption and fluorescence techniques in different pH media, and showed that 2 could bind to CT-DNA presumably via non-intercalative mode and the La(III) complex showed moderate ability to bind CT-DNA compared to other La(III) complexes. The binding site number n, and apparent binding constant KA, corresponding thermodynamic parameters ΔG#, ΔH#, ΔS# at different temperatures were calculated. The binding constant (KA) values are 0.23 ± 0.05, 0.56 ± 0.05, and 0.18 ± 0.08 × 105 L mol-1 for pH 4, 7, and 11, respectively. It was also found that the fluorescence quenching mechanism of CT-DNA by La(III) complex was a static quenching process.
CRIS-Team Scopus Importer:2026-01-22
Keywords: DNA-binding; Excitations; Fluorescence spectra; La(III) complexes; Norfloxacin